Ghosts of terror wars past?: crime, terror and America’s first clash with the Saracen hordes - Naylor, Robin T. (Crime, law and social change, 2006)
In the wake of 9/11 and the invasion of Afghanistan, then of Iraq, with all the talk of a renewed Clash of Civilizations, came a revival of interest in the lessons from what seemed to be the direct antecedent, namely the Barbary Wars of the late 18th and early 19th centuries. At that time, too, America had seemed to be forced to defend itself economically and militarily against a fanatical foe which rationalized crimes in the name of religion to wage terror against innocents. There are indeed close analogies between the two; but they are almost exactly the opposite of what much popular (and some official) belief holds true. If today it has become clear that most justifications for the current Terror War were fabrications intended to cloak other agendas at home and abroad, when the Barbary Wars are subjected to serious scrutiny, much the same forces advancing much the same agendas appear at work. Nor are the "politics of fear" new in American history. During the Barbary Wars, carefully cultivated fears of a rising Islamintern served to: divert public attention from domestic political problems; suppress political dissent; provide cover for regressive fiscal changes; cloak offensive militarism in defensive guise; and ride roughshod over both conventions of international diplomacy and normal standards of criminal justice, all rationalized by a sense of Christian mission.